Write portable code : an introduction to developing software for multiple platforms - Hook, Brian, 1971- (No Starch Press, 2005)
Write Portable Code contains the lessons, patterns, and knowledge for developing cross-platform software that programmers usually must acquire through trial and error. This book is targeted at intermediate- to advanced-level programmers and will be a valuable resource for designers of cross-platform software, programmers looking to extend their skills to additional platforms, and programmers faced with the tricky task of moving code from one platform to another.